IMPLEMENTASI KEPEMIMPINAN MANAJERIAL KEPALA MADRASAH DAN KINERJA GURU DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA DI MTs MANBAUL ULUM KECAMATAN LEMPUING JAYA KABUPATEN OGAN KOMERING ILIR SUMATERA SELATAN PELAJARAN 2023/2024 - Muhammad Nurudin (UNISAN JURNAL, 2024)
The leadership of the head of the madrasa at MTs Manbaul Ulum, Lempuing Jaya District, Ogan Komering Ilir Regency, South Sumatra is quite good. He is responsible for the institution at MTs Manbaul Ulum, Lempuing Jaya District, Ogan Komering Ilir Regency, South Sumatra. This research uses a qualitative approach. While the method used in this research is descriptive research method. The data collection technique used is observation, interview and documentation techniques. This participatory observation technique was carried out to observe the geographic location in the form of a location plan and environmental conditions, vision, mission, strategy and motto of the school as well as the condition of human resources at MTs Manbaul Ulum, Lempuing Jaya District, Ogan Komering Ilir Regency, South Sumatra. Interviews were conducted to find out the leadership of the madrasah head in teacher performance. Based on the results of the description that has been described, the leadership of the madrasa head in teacher performance cannot be separated from Team Work (cooperation) with the help of supporting resources. Implementation with a certain strategy that is effective and efficient, and refers to the vision, mission and goals that have been determined previously. the style used by the headmaster of the madrasa to lead is by using a democratic style, namely where the headmaster always draws closer to the teachers, students and madrasa employees with the aim of guiding or protecting the teachers so that they carry out their duties and obligations. Teachers have good performance in the learning process, this can be seen from the process of preparing lesson plans that are arranged according to the criteria set out in teacher performance standards